Giant urethral calculus associated with urethrocutaneous fistula: a case report - Das, Narayan; Chatterjee, Damodar (International Journal of Research in Medical Sciences, 2017)
Urethral stones in men are rare clinical entity and most of them migrate from urinary bladder. Giant urethral calculi are extremely rare. This report describes the case of 62 year male patient presenting with giant bulbar urethral calculus associated with urethrocutaneous fistula.